Ca-free hemodialysis as a parathyroid function test in chronic renal failure patients on maintenance hemodialysis - Inoue, Seishi; Fujita, Yoshikazu; Hirabayashi, Toshiaki; Azuma, Masayuki (Journal of Japanese Society for Dialysis Therapy, 1992)
Parathyroid hormone (PTH) response to hypocalcemia was studied in 16 hemodialysis patients with different levels of parathyroid function. There were 10 patients with normal parathyroid function, 3 with severe hyperparathyroidism, 4 who had undergone parathyroidectomy and 4 who were aparathyroid. Hypocalcemia during hemodialysis was produced by Ca-free hemodialysis for 60 min followed by the use of Ca 3.5mEq/l dialysate for 240 min. Serum total Ca and ionized Ca showed the lowest levels during the test at 60 min. Intact-PTH patients attained maximum levels at 30 or 60 min after Ca-free HD. The differences in changes according to group were as follows. The 10 patients with clinically normal parathyroid function exhibited a mild increase in intact-PTH (Δintact-PTH 110 pg/ml). The 3 patients with severe hyperparathyroidism exhibited a marked increase in intact-PTH (Δintact-PTH 400-1, 000 pg/ml) and, after PTX, the patterns became normal. The 2 aparathyroid patients showed no response to hypocalcemic stimulation, and their PTH levels remained in the very low range. In conclusion, hypocalcemic stimulation during Ca-free hemodialysis is useful in evaluating the level of parathyroid function in chronic renal failure patients on hemodialysis.